Pengaruh Pemasaran Media Sosial di Instagram @kopijanjijiwa terhadap Keputusan Pembelian Konsumen - Wibisono, Daeng Mohammad Danu; Wibowo, Tangguh Okta (UNIVERSITAS KALBIS, 2024)
Social media marketing is one of the important aspects in increasing sales of a product. Because social media marketing uses social media as a marketing channel and there are quite a lot of social media users in Indonesia. This study aims to determine the influence and level of influence of social media marketing on Instagram @kopiunjukjiwa on consumer purchasing decisions. In this study, the theory used is stimulus-response. The researcher uses a quantitative approach, survey research method with explanative type. The population in this study were followers of Instagram @kopiunjukjiwa with questionnaire data collection techniques. Based on the results of the hypothesis with the T test, the results obtained are 21,161 > 1,966. from these results indicate that social media marketing on Instagram @kopipromisejiwa has an influence on consumer purchasing decisions. Meanwhile, Pearson's product moment got a result of 0.728, which means that there is a strong influence from social media marketing on Instagram @kopikodejiwa on consumer purchasing decisions, and the coefficient of determination test got a result of 52.9%.